(untitled) (Revista Cientifica Ingenio Magno, 2022)
This work shows how a tool related to industry 4.0 was developed and its implementation to be used in teaching-learning processes, especially in the area of industrial automation of the Faculty of Mechatronics Engineering of the Universidad Santo Tomás - Bucaramanga Seccional Colombia. This tool was made following the methodology of analysis, foundation, design and finally an implementation. The tool has been made through a local web page and a mobile application in charge of controlling, storing, generating reports and issuing data obtained by a Siemens s7-1200 PLC controller, from an instrumented industrial pilot plant. The page stores an interface for an initial didactic control, to generate reports from a MySQL database and an interface in charge of monitoring with a supervision system (SCADA). The mobile application runs on Android and has interaction interfaces for the control and monitoring of information through augmented reality, with which it is possible to observe the symbols of the elements of an industrial pilot plant and thus select and issue or receive data from the selected device. In addition, the application allows you to interact to obtain information on each particular element.